The CSS3 anthology take your sites to new heights, fourth edition - Andrew, Rachel (SitePoint Pty. Ltd., 2012)
The CSS3 Anthology: 101 Essential Tips, Tricks & Hacksis a compilation of best-practice solutions to the most challenging CSS problems. The fourth edition of this best-selling full-color book has been completely revised and updated to cover newer techniques enabled by CSS3 and HTML5, and more recent trends in web design, such as responsive design. It's the most complete question-and-answer book on CSS available, with over 100 tutorials that show readers how to gain more control over the appearance of their web pages, create sophisticated web page navigation controls, and design for alternative browsing devices, including phones and screen readers. The CSS code used to create each of the components is available for download and guaranteed to be simple, efficient and cross-browser compatible.
Includes bibliographical references and index
Keywords: Cascading style sheets; Web sites -- Design; Cascading style sheets -- Handbooks, manuals, etc; Web site development -- Handbooks, manuals, etc -- Computer programs; Web sites -- Handbooks, manuals, etc -- Design; Web sites -- Handbooks, manuals, etc -- Authoring programs; Feuilles de style en cascade; Guides, manuels, etc; Sites Web; Systèmes-auteur; Guides, manuels, etc; Sites Web; Conception; Guides, manuels, etc; Feuilles de style en cascade; Sites Web; Conception; COMPUTERS; Digital Media; General; COMPUTERS; Interactive & Multimedia; COMPUTERS; Web; Site Design; COMPUTERS; Web; User Generated Content; Web site development; Computer programs; Web sites; Design; handbooks; Handbooks and manuals; Guides et manuels